HIGH-DENSITY POLYETHYLENE CARCASS WRAPPING DURING THE FIRST 24 HOURS POST-MORTEM AND ITS EFFECTS ON RABBIT MEAT QUALITY - Dutra, Daniel Rodrigues [UNESP]; Villegas-Cayllahua, Erick Alonso [UNESP]; Feliciano, Andresa Lazzarotto [UNESP]; Borba, Hirasilva [UNESP] (Universitat Politecnica de Valencia, 2024)
Post-slaughter chilling is essential for food safety in the meat industry. However, carcasses exposed to cold air in refrigerated chambers may undergo adverse effects on quality parameters. Thus, this study aimed to evaluate the efficiency of high-density polyethylene (HDPE) plastic wrapping on rabbit carcasses during post-slaughter chilling and its impact on the rabbit meat quality. Twenty whole carcasses of male Botucatu rabbits, slaughtered at 90 days of age, were used in a completely randomised design with a 2×2 factorial scheme [HDPE carcass wrapping (present and absent) vs. cut (loin vs. thigh)]. After 24 h of slow chilling at 4°C, the carcasses were deboned and physicochemical analyses were conducted to assess quality parameters: pH, colour (L*, a*, b*), water-holding capacity (WHC), cooking loss (CL), sarcomere length (SL), shear force (SF), myofibrillar fragmentation index (MFI) and lipid oxidation by thiobarbituric acid reactive substance (TBARS). The wrapping resulted in lower (P<0.05) ultimate pH, red intensity, water-holding capacity and shear force, and higher MFI (P<0.05). Sarcomere length was shorter in the unwrapped thigh compared to both wrapped thigh and unwrapped loin (P<0.05). The thigh exhibited higher redness, yellowness and shear force (P<0.05), while the loin showed greater lightness (P<0.05). The unwrapped loin also demonstrated a greater MFI than the unwrapped thigh (P<0.05). Notably, no significant effect of either wrapping or cut type was observed on TBARS (P>0.05). These findings demonstrated that HDPE wrapping maintained the light colour of rabbit meat, which is more appealing to white meat consumers due to its light pink appearance. Additionally, HDPE wrapping enhanced tenderness, a key attribute in consumers’ meat selection, as indicated by higher MFI values (P<0.05) and lower shear force measurements (P<0.05). In conclusion, wrapping carcasses in high-density polyethylene during the first 24 h post-mortem positively influences the rabbit meat quality, particularly in terms of colour and tenderness, with the loin cut showing superior tenderness compared to the thigh.
Keywords: meat colour; myofibrillar fragmentation index; rabbit production; sarcomere length; shear force; tenderness